BANTUAN HUKUM YANG IDEAL BAGI MASYARAKAT TIDAK MAMPU - Supriyatna, Dadang (JURNAL ILMIAH LIVING LAW, 2018)
This study analyzes the importance of the position of advocates in the legal system in Indonesia. Advocates have a very important role in law enforcement. The defense for all people, including the community, is a manifestation of an advocateâs respect for the principle of equality before the law as well as the realization of the rights of all people, namely the right to be accompanied by an advocate. The purpose of the research is to (1) find out the position and role of advocates in the implementation of human rights in Indonesia, (2) Analyze the barriers of advocates in realizing their position and role. The research method used is qualitative and normative juridical ap- proach, namely law is conceived as a norm, rule, principle or dogmas / juris- prudence. The normative juridical research phase uses literature studies. The results of the study indicate that Advocates have a very important position and role as one of the elements of the Preacherâs Legal Chess, because of the status of free and independent advocates guaranteed by law and regulation, For the sake of legal interests and demands for professions that have social aspects, every the person involved in the case has the right and guaranteed access to legal assistance. Other results indicate factors that prevent advocates from realizing their position and role related to the normative level, namely the absence of specific legal aid arrangements that regulate the entire scope of the provision of legal assistance.